Emerging Role of Consolidative Radiotherapy After Complete Remission Following R-CHOP Immunochemotherapy in Stage III–IV Diffuse Large B-Cell Lymphoma: A Single Institutional and Case-Matched Control Study - Hong, Ji Hyun; Lee, Han Hee; Jung, Seung-Eun; Park, Gyeongsin; O, Joo-Hyun; Jeon, Young-Woo; Choi, Byung-Ock; Cho, Seok-Goo (Frontiers in Oncology, 2021)
Purpose The role of consolidative radiotherapy (RT) after complete-remission (CR) following rituximab combined with cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) in advanced-stage diffuse large B-cell lymphoma (DLBCL) remains unclear. We retrospectively analyzed the survival outcomes and patterns of failure with our institutional experience. Material and Methods Between 2009 and 2018, 206 patients with stage III-IV DLBCL achieved CR after receiving R-CHOP. Propensity-score matching was used to analyze the role of consolidative RT. The consolidative RT group (n=34) and the R-CHOP alone group (n=68) were matched at a 1:2 ratio. After propensity-score matching, 102 patients were analyzed. Results With a median follow-up of 39.7 months, 26 patients (25.5%) showed local recurrence. Only one patient failed at the previous RT field. RT was delivered to bulky sites, head and neck lesions, testes and bone with median dose of 30.6Gy. The most common site of failure was head and neck lesions followed by bulky sites. The 5-year overall survival (OS), progression-free survival (PFS), and isolated-local recurrence free survival (LRFS) were 73.5%, 64.0%, and 79.9%. In univariate and multivariate analysis, bone marrow involvement and consolidative RT were associated with isolated LRFS (p=0.006 and 0.032) significantly. Conclusion Consolidative RT improved isolated local control. Based on the pattern of failure, we carefully suggest to radiate on initially involved bulky sites or head and neck lesions. Further studies need to be done to find out the optimal radiation dose and selection of RT site.